Assistive System to Improve Pedestrians' Safety and Mobility in a Connected Vehicle Technology Environment. Issue 19 (December 2018) - Khosravi, Sara; Beak, Byungho; Head, K. Larry; Saleem, Faisal
Conflicts between vehicles and vulnerable road users (VRUs) often result in injuries and fatalities. This paper presents a vehicle-to-infrastructure and Wi-Fi based pedestrian conflict avoidance system to improve VRUs' safety. Compared with the vision based systems, the proposed system can improve VRUs' safety in non-line-of-sight situations. In particular, it can be helpful in a situation when drivers are making a right or left turn where there is a crosswalk and visibility conditions are poor. The system, called Smart Walk Assistant (SWA), was implemented as an application on a smartphone and server on a roadside unit. It includes two wireless communication pathways: pedestrian-to-infrastructure (P2I) and pedestrian-to-vehicle (P2V). The first communication pathway enables users to send a pedestrian signal request to the traffic signal controller and receive traffic signal status. The second communication pathway enables pedestrians and vehicles to exchange information including location, speed, and heading that can be used to provide conflict alerts. The SWA system may be especially beneficial to differently abled pedestrians, including blind or visually impaired pedestrians, who would benefit from active support to safely cross streets at signalized intersections. The P2I application was designed, developed, and field demonstrated. The P2V application was designed and developed, and will be field tested in the near future.